042 Opportunities and challenges of remote neurological outpatient consultations. Issue 6 (27th May 2022) - Hogan, Joseph; MacDonald, Bridget; Mastrolilli, Francesca; Nitkunan, Arani
Abstract : Croydon University Hospital: Remote consultations were rapidly introduced in the spring of 2020 in the neurology outpatient setting across the UK and worldwide due to the Covid-19 pandemic. Consulting remotely provides new chal- lenges to previously familiar practices. Here we present four different but commonly seen cases in a south London outpatient neurology service. With each case we address a key domain: history taking, examina- tion, the digital divide and changing the consulting environment. History taking is largely unchanged and indeed may improve the patient experience when performed in a familiar environment. The examina- tion is different and a greater understanding of which aspects of the neurological exam are and are not possible remotely continues to be discussed. The adoption of remote consultations requires patients to have a confident ability to activate and interact with technologies. The future development of technolo- gies and guidelines should proactively engage with patients of all ages and abilities to avoid biases in their development. Remote consultations are likely to continue to play a part in the future of outpatient neurology; understanding their most effective allocation and proactively developing technologies with patients will be essential for their success. joseph: hogan1@nhs.net|ABN Bursary 46